Expanding commodity frontiers and the emergence of customary land markets: A case study of tree-crop farming in Venda, South Africa. (February 2021) - Olofsson, Malin
Highlights: Commodification of tree crops amongst smallholders is transforming customary land rights. Customary land rights for orchards have become increasingly individual and exclusive. Access to customary land rights for orchards are becoming increasingly based on financial transactions. New opportunities are emerging for rent appropriation by undemocratic traditional authorities. A small-minority of tree-crop farmers are fast accumulating land as the expense of other land users. Abstract: Contemporary discourses on customary land tenure in Africa, and South Africa in particular, have emphasized the socially embedded and flexible nature of customary land rights, recognising these as inherently more 'pro-poor' than individual titling. Based on in-depth interviews and participant observations in Venda, a former homeland in South Africa, this paper explores how in the context of expanding commodity frontiers, customary land markets have emerged, leading to de facto privatisation of customary land. This presents new opportunities for rent appropriation by traditional authorities and emergent processes of land accumulation by a minority of smallholder farmers as land rights in relation to orchards have become increasingly individual and exclusive, with access and use rights linked primarily to financial transactions. This paper argues that the increasing de facto privatisation of land within communal areas and its specific character needs to be recognised, and traditional leaders made more downwardly accountable when it comes to land governance, if an inclusive and socially just system of customary land governance is to be achieved.